Hadith-Based Legal Reasoning in MUI Fatwas during the COVID-19 Pandemic: Between Prophetic Traditions and Maqāṣid al-Sharī‘ah - A Halil Thahir; Niwari (LPPM UIN Syekh Wasil Kediri, 2025)
This research examines the fiqh of priorities in the fatwas of the Indonesian Ulama Council during the COVID-19 pandemic. The problem presented in it is : What are the areas of the fatwas of the Indonesian Ulama Council during the COVID-19 pandemic? How does the Indonesian Ulama Council issue a fatwa during the COVID-19 pandemic from the perspective of the fiqh of priorities? This research is desk research. Its data is available from library sources, both major and bilateral. The method of collecting data is documentary, which means collecting it in writing. The method of analyzing it is the content analysis that the researcher uses in analyzing the fiqh of priorities in the fatwas of the Indonesian Ulama Council during the COVID-19 pandemic. During the COVID-19 pandemic, various religious practices and rituals have been restricted or even postponed, preventing the spread of the virus. In this context, the Indonesian Ulema Council (MUI) issued a number of fatwas, including an important fatwa on 16 March 2020, shortly after the first case of COVID-19 was announced in Indonesia. This study aims to examine the hadith-based legal reasoning in the MUI's fatwas during the COVID-19 pandemic by highlighting the relationship between hadith arguments and the maqāṣid al-sharī‘ah framework through the fiqh al-awlawiyyāt (fiqh of priorities) approach. This study is a literature review using primary and secondary sources. Data was collected through documentation and analysed using content analysis to identify patterns of use, interpretation, and prioritisation of hadiths in MUI fatwas. The results of the study show that MUI fatwas during the pandemic cover three main areas, namely worship, individual, and socio-religious. MUI's legal reasoning shows consistency in prioritising hadiths oriented towards the protection of life (ḥifẓ al-nafs), prevention of harm, and public interest. These hadiths are operationalised contextually through the principle of maqāṣid al-sharī‘ah, resulting in fatwas that are responsive to health emergencies without negating the normative authority of hadith. Keywords: Fatwa of the Indonesian Ulama Council, COVID-19, fiqh of priorities, the Quran, Hadits